Physical attributes on place attachment in Malaysian urban parks - Ebadi, Hadi (2015)
Well-designed and properly equipped parks including physical attributes have resulted in a significant increase in the level of place attachment and the visitation rates of urban parks and recreation areas. The relationship between individuals and places is known as place attachment. The lack of parks’ physical attributes, special characteristics as well as internal and surrounding environment of the parks are the factors prohibiting visitors’ experiences to the parks. Moreover, fast urbanization in Malaysia leads to the lack of allocated areas and physical attributes for open spaces and urban parks in the cities. Therefore, place attachment and park visitation within the urban parks in Malaysia has been decreased. In the present study, the relationship between parks environment and visitors’ requirements is examined, in order to improve their attachment and visitation to parks. To this end, it aims to scrutinize this phenomenon by investigating the influence of physical attributes on the level of place attachment and visitation rates of Malaysian urban parks. In this study, a model for the physical attributes is constructed comprising two dependent variables, i.e. place attachment and park visitation which are connected through place satisfaction. The model can contribute to a better understanding of physical attributes and its role in user attachment and visitors. To answer the research questions, a questionnaire was designed. Three parks in different states of Malaysia were selected to be evaluated according to experts rating and a pilot study. To gain initial information on the topic, several observations were carried out to identify the physical attributes of the parks as well as to observe the subjects prior to designing questionnaires. Stratified random sampling was employed to collect data from a sample of 400 visitors of various age groups visiting the park. The participants were selected randomly from those who use the park. The collected data were analysed using structural equation modelling (SEM) and smart PLS software. The results showed that, four dimensions of place attachment are existing in Malaysian urban parks and physical attributes directly affect to increase the level of place attachment and rate of visitation; also the physical attributes such as walking path, trees and jogging track as the main attributes affecting people to attending the urban parks. The findings raise the awareness of urban planners and designers’ attention to the pivotal role of the physical attributes in providing more beautifully landscaped parks for the visitors. This will contribute to the stronger place attachment and higher visitation rates of the parks in Malaysia.